Analisis Penerimaan Informasi Kekayaan Intelektual dan Akuntabilitas Dokumen (INTIPDAQU) oleh Arsiparis Badan Riset dan Inovasi Nasional (BRIN) menggunakan Technology Acceptance Model (TAM) - Aulianto, Dwi Ridho; Anggoro, Wahyu Tri; Raharja, Tiara Desyanti; Hermansyah, Dendang (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2024)
Background: Recent research on the use of digital platforms for managing protected archives highlights a gap in understanding archivists' perceptions of these technologies.Objective: This study aimed to explore the perceptions of archivists within the BRIN (National Research and Innovation Agency) regarding the INTIPDAQU (Information Tracer of Intellectual Property & Document Accountability Inquiry) application, addressing the knowledge gap related to the transition from conventional to digital archive management.Methods: A quantitative approach was used, with a survey design. Data were analyzed using regression analysis to assess the relationships between Perceived Usefulness, Perceived Ease of Use, attitudes toward use, and behavioral intention.Results: The study found that 68.2% of the variation in attitudes toward use can be explained by Perceived Usefulness, while 59.8% of the variation is influenced by Perceived Ease of Use. A significant effect of Perceived Ease of Use on Perceived Usefulness was observed, with an R Square value of 0.517. Additionally, 61.7% of the variation in behavioral intention can be explained by attitudes toward useConclusion: These results indicate that Perceived Usefulness and ease of use are crucial in shaping positive attitudes and intentions to use the INTIPDAQU application among archivists. Further research should focus on analyzing the long-term impact of using the INTIPDAQU application on the work efficiency of archivists and its contribution to broader archive management.